Marketing Strategy for Ratna Collection - Tufani, Irni; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2015)
Abstract - Indonesia is one of the new engines of luxury growth within Asia region. Luxury goods growth in Indonesia is estimate could rise to 40%-60% annually. Indonesia is very attractive country for luxury good brands because number of consumer who can afford luxury goods are increasing. Ratna Collection is providing luxury goods such as bags, watches, glasses, accessories, fragrance, etc. The company objective is to be growing and profitable company. This research focus on marketing issues that consist of decreasing number of visitor, low brand awareness and lack of market research activities. The purpose of this research is to define the target market and get appropriate marketing strategy based on marketing mix. Based on root cause analysis, decreasing number of visitor are caused by unclear target market and not appropriate marketing strategy. Data analysis resulted that Ratna Collection should renewal STP and marketing mix. By conducting clustering, discriminant analysis method and also interview with the owner, the best target market and appropriate marketing strategy for Ratna Collection were decided